Peningkatan Literasi Finansial Berkelanjutan Melalui Edukasi Dan Pendampingan Dalam Pengelolaan Keuangan Masyarakat Desa Jayaraga - S, Taufik Maulana; Kamila, Alya; Anggraeni, Shinta; Oktapiani, Silmi; D, Haifa Zahra; Rahmasri, Fanny; Gusmitasari, Tiara; Khairunnisa, Khansa; P, Andhika Deska; Pratama, Rizqan; Permana, Reza Dwi (Amirul Bangun Bangsa, 2024)
Financial literacy is an essential skill that the community needs to possess in order to achieve economic well-being. However, there are still many people in rural areas with low financial literacy levels, including in Jayaraga Village. This research aims to enhance financial literacy sustainably through seminars, workshops, case studies, and focus group discussions. The method used in this research is a participatory approach, where the community is actively involved in every stage of the activities, from basic financial literacy training to assistance in implementing good financial practices. The results of the study indicate an increase in the community's understanding of basic financial concepts, including budgeting, debt management, and simple investments. In addition, this program has also succeeded in raising public awareness about the importance of financial literacy in achieving family economic stability. With continuous education and guidance, it is hoped that the financial literacy of the people in Jayaraga Village can continue to develop and have a positive impact on the local economy.